Respuesta :

Question:

Solution:

The entire circumference is equivalent to traveling 360 degrees. Therefore, we have the following equation:

[tex]83+62+(5x-13)+(6x-36)\text{ = 360}[/tex]

this is equivalent to:

[tex]83+62-13-36+(5x+6x)\text{ = 360}[/tex]

this is equivalent to:

[tex]96\text{ +11x = 360}[/tex]

this is equivalent to:

[tex]11x\text{ = 360-96 = 297}[/tex]

and solving for x, we obtain:

[tex]x\text{ = }\frac{264}{11}=\text{ 2}4[/tex]

then, the correct answer is:

[tex]x\text{ = 2}4[/tex]

Ver imagen KaysonF203701